Pengaruh Pemanfaatan Fintech dan Kemudahan Akses Bayar terhadap Penggunaan PLN Mobile pada PT PLN (Persero) UP3 Makassar Selatan - Sarah Sarah; Muryani Arsal; Muhammad Nur Abdi (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of digital technology has encouraged PT PLN (Persero) to continuously improve service quality through the PLN Mobile application integrated with financial technology (fintech). This study aims to analyze the effect of fintech utilization and ease of payment access on the use of the PLN Mobile application at PT PLN (Persero) UP3 Makassar Selatan. This research employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to PLN Mobile users and analyzed using multiple linear regression. The results indicate that fintech utilization and ease of payment access have a positive and significant effect on the use of the PLN Mobile application, both partially and simultaneously. These findings suggest that convenience, security, and the effectiveness of digital payment services are important factors in increasing customers’ interest and intensity in using the PLN Mobile application. Furthermore, the integration of responsive and easily accessible digital services strengthens customer trust in application-based payment systems. This study is expected to serve as a reference for the company in developing more innovative, efficient, and customer-oriented digital service strategies in a sustainable manner.